2008
DOI: 10.1057/emr.2008.27
|View full text |Cite
|
Sign up to set email alerts
|

Comment: Further considerations on the relevance of country‐of‐origin research

Abstract: This paper is a reply to the paper by Josiassen and Harzing about the continued relevance of country‐of‐origin (COO) research in marketing (forthcoming, EMR). It develops detailed and articulated responses to each of their arguments. Although sharing some of Josiassen and Harzing's views, this reply maintains that the case of COO research raises significant issues in terms of its relevance to marketing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 12 publications
2
35
0
1
Order By: Relevance
“…This is consistent with other research suggesting that products from developed countries have higher quality than those from developing countries (Pappu et al, 2007;Usunier & Cestre, 2008). However, the many differences between developed and developing countries in socio-economic, demographic and other factors may lead to more complex differences in the PCIs of developed and developing countries (Batra, 1997;Cui & Liu, 2001).…”
Section: Pci In Developed and Developing Countriessupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with other research suggesting that products from developed countries have higher quality than those from developing countries (Pappu et al, 2007;Usunier & Cestre, 2008). However, the many differences between developed and developing countries in socio-economic, demographic and other factors may lead to more complex differences in the PCIs of developed and developing countries (Batra, 1997;Cui & Liu, 2001).…”
Section: Pci In Developed and Developing Countriessupporting
confidence: 91%
“…However, although there are some studies that have examined the influence of country development status on PCI, they remain few in number and the results to date have been inconclusive. Some papers have shown that consumers perceive products from developing countries to have lower quality than those from developed countries (Ö zsomer, 2012;Pappu, Quester, & Cooksey, 2007;Usunier & Cestre, 2008). Other studies have suggested that the increase in off-shore manufacturing in developing countries may have altered such perceptions (Chao, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it offers evidence regarding the relative strength of these constructs as drivers of brand attitude, thus highlighting the relevance of the respective theoretical domains. Moreover, by approaching the COO construct through the lenses of the SCM, the study contributes toward a more theoretically driven investigation of COO effects, commonly criticized for lacking substantive theoretical backing (Samiee, 2011;Usunier & Cestre, 2008). Importantly, to the best of our knowledge, this study represents the first empirical attempt to explore the potential interplay between stereotypical judgments of the brand origin and consumers' perceptions of the globalness/localness of a brand.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, Usunier (2006, p. 61) argues that the "COO effect is no longer a major issue in international marketing operations: multinational production, global branding, and the decline of origin labelling in WTO rules tend to blur the COO issue and to lessen its relevance." Moreover, COO research has been criticized for lacking a solid theoretical background (Usunier & Cestre, 2008) and for being "generally void of meaningful managerial guidelines" (Samiee, 2011, p. 473). On the other hand, some authors challenge the notion of universal and unconditional global brand preference (Riefler, 2012), while others suggest that the COO is a salient factor in consumer evaluations even in an era of global brand prevalence (Wilcox, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…COO studies have argued that consumers have diverse perceptions about products or services made in or associated with foreign countries, and that these perceptions affect their behavior based on stereotyped national images of the country of association. Extensive empirical research has been completed in this area throughout the past fifty years, concluding that COO effects do exist and they have considerable impact on product quality evaluations and purchase intentions (e.g., Bilkey and Nes, 1982;Cordell, 1992;Tse and Gorn, 1993;Papadopoulos and Heslop, 2002;Usunier and Cestre 2008). In fact, the COO effect on consumers is one extrinsic cue that has grown increasingly significant as the trend towards globalization of production and multinational enterprise (MNE) strategy has intensified, particularly for those from emerging markets such as Taiwan, China and India.…”
Section: Introductionmentioning
confidence: 99%